Pengembangan Booklet Zoologi Vertebrata Terintegrasi TPACK: Studi Pendahuluan dengan Model Plomp - Fauziah, Nurul; Ade Rahma Yulis, Putri; Fitri, Rhada Hasanah; Erfina , Erfina (Perspektif Pendidikan dan Keguruan, 2025)
This research aims to describe data from the preliminary research stage as a basis for developing a Vertebrate Zoology booklet integrated with the TPACK approach. This research uses a development method with the Plomp model, which only focuses on the first stage, namely the preliminary research phase. The research sample consisted of 90 Biology Education students, FKIP UIR. The instruments used include RPS analysis sheets, interview sheets, observation sheets, and questionnaires to identify student problems and needs. The research results showed that from the RPS analysis, eight main topics were studied, and 8.88% of respondents stated that there were no Vertebrate Zoology learning media based on specific approaches, methods, or learning models. In addition, based on the results of the needs questionnaire, 100% of students expressed support for the developing Vertebrate Zoology booklet integrated with TPACK. Based on the data obtained at the preliminary research stage, it can be concluded that the development of a TPACK-based Vertebrate Zoology booklet needs to be carried out to increase learning effectiveness.